1980
DOI: 10.1073/pnas.77.5.2569
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of duplex DNA containing single-stranded regions by recA protein.

Abstract: Genetic recombination in Escherichia coli requires recA protein, the product of the recA+ gene. In this paper we show that purified recA protein, which binds strongly to denatured DNA, cooperatively recognizes DNA containing short single-stranded regions. The interaction of varying amounts of recA protein with DNA molecules was investigated by measuring its DNA-dependent ATPase activity. In 3 mM Mg2+, the ATPase activity was stimulated by excess singlestranded DNA The recA + gene product plays an indispensab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0

Year Published

1981
1981
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(44 citation statements)
references
References 27 publications
(10 reference statements)
2
42
0
Order By: Relevance
“…The invasion of duplex DNA by single-stranded homologous DNA is stimulated in vitro by the addition of purified recA protein (3). Other studies support the conclusion that with the addition of ATP, this protein facilitates reciprocal strand transfer between two double helices (18).…”
supporting
confidence: 55%
“…The invasion of duplex DNA by single-stranded homologous DNA is stimulated in vitro by the addition of purified recA protein (3). Other studies support the conclusion that with the addition of ATP, this protein facilitates reciprocal strand transfer between two double helices (18).…”
supporting
confidence: 55%
“…In vitro studies revealed the following steps for the formation of the joint molecules by RecA protein: (i) in the presence of ATP (or its unhydrolyzable analogue, ATP␥S), RecA protein cooperatively polymerizes along single-stranded DNA (15)(16)(17), resulting in the formation of ''presynaptic filaments'' in which the DNA is extended up to 1.5-fold compared with B-form DNA with the same sequence (18,19); (ii) the presynaptic filament captures double-stranded DNA to search for homology to the singlestranded DNA present in the filament and upon homologous alignment of the DNA molecules a core heteroduplex is formed (the completion of homologous pairing; 15,18,20,21); and (iii) the core heteroduplex is unidirectionally extended and stabilized by strand exchange (12,22,23; see also refs. 24-30 for review).…”
mentioning
confidence: 99%
“…la), but not to cover all the double stranded regions for DNA concentrations higher than 5 ug/ml. We have previously suggested that recA protein binds to single stranded DNA and spreads onto the adjoining duplex in a gapped molecule (6).…”
Section: Resultsmentioning
confidence: 99%
“…The purification of recA protein has been described (6 1.25 ;zg of gapped 3H-DNA were incubated with 0.1 to 0.8 mg/ml of recA protein in 50 pl of 33 mM Tris. HCl, pH 7.5, 25 mM MgCl2, 2mM dithiothreithol, 100 pg/ml bovine serum albumin (BRL) and 1.2 mM ATP.…”
Section: Materials and Methods Enzymes And Proteinsmentioning
confidence: 99%
See 1 more Smart Citation